Resin composition, prepreg, film with resin, metal foil with resin, metal foil-clad laminate, and wiring board
By using a resin composition containing maleimide compounds, imide compounds and free radical polymerizable compounds, the problem of poor dielectric properties of wiring board insulating layer materials in the prior art under high frequency environment is solved, and the dielectric properties of wiring board insulating layer materials are achieved. A resin composition with low dielectric constant and dielectric loss factor and good water absorption stability is provided.
Patent Information
- Application Number
- CN202380049491.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-04
- Filing Date
- 2023-06-26
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to obtain wiring board insulation layer materials for electronic equipment in high-frequency environments. The relative dielectric constant and dielectric loss factor are low, and the increase in dielectric characteristics caused by water absorption is sufficiently suppressed, while the thermal expansion coefficient is at the same time. Also low.
A resin composition is used, which contains a maleimide compound (A), an imide compound (B) and a radical polymerizable compound (C), wherein the maleimide compound has benzene in the molecule The ring, the imide compound has a hydrocarbon group and a maleimide group at the end of the molecule, and the weight average molecular weight of the radical polymerizable compound is 1,000 or less.
The cured product of the resin composition with a low relative dielectric constant and dielectric loss factor in a high frequency environment is realized, and the dielectric characteristics caused by water absorption are suppressed, and the dielectric characteristics are increased, and the thermal expansion coefficient is low.
Smart Images

Figure BDA0005205997660000041 
Figure BDA0005205997660000042 
Figure BDA0005205997660000051
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a prepreg, a film with a resin, a metal foil with a resin, a metal foil-clad laminate, and a wiring board. Background Art
[0002] For various electronic devices, as the amount of information processing increases, the high integration of semiconductor devices, high density of wiring, and multi-layer installation technology are rapidly developing. In addition, wiring boards used in various electronic devices, such as antenna packaging substrates in mobile applications, are required to cope with high frequencies. In order to increase the transmission speed of signals and reduce the loss during signal transmission, the substrate material used to form the insulating layer of the wiring board used in various electronic devices is required to have a low relative dielectric constant and dielectric loss factor.
[0003] Examples of substrate materials for forming the insulating layer of the wiring board include resin compositions described in Patent Documents 1 and 2.
[0004] Patent document 1 describes a resin composition, which includes: a modified polyphenylene ether compound whose terminal is modified by a substituent having a carbon-carbon unsaturated double bond; a maleimide compound that does not contain a phenylmaleimide group and has a hydrocarbon group with a carbon number of 10 or more in the molecule; and at least one selected from a maleimide compound containing a phenylmaleimide group and a maleimide compound having an aliphatic hydrocarbon group with a carbon number of 9 or less in the molecule. According to patent document 1, it is disclosed that a resin composition can be provided, which has both: the operability of a prepreg containing the resin composition or its semi-cured product; and the low dielectric properties, high heat resistance, high Tg, low thermal expansion coefficient, adhesion and low water absorption of the cured product of the resin composition.
[0005] Patent Document 2 describes a resin composition containing a compound having a maleimide group, a divalent group having at least two imide bonds, and a saturated or unsaturated divalent hydrocarbon group. Patent Document 2 discloses a resin composition that can provide excellent high-frequency characteristics (low relative dielectric constant, low dielectric loss factor) and also has high levels of adhesion to conductors, heat resistance, and low hygroscopicity.
[0006] The substrate material used for the insulating layer of the wiring board is required to have not only low relative dielectric constant and dielectric loss tangent, but also sufficiently suppress the increase of relative dielectric constant and dielectric loss tangent due to water absorption and to be able to obtain a cured product with a low thermal expansion coefficient.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Patent Publication No. 2019 / 188189
[0010] Patent Document 2: International Patent Publication No. 2016 / 114286 Summary of the invention
[0011] The present invention is an invention completed in view of this situation, and its purpose is to provide a resin composition that can obtain a cured product with low relative dielectric constant and dielectric loss factor, in which the increase of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. In addition, the purpose of the present invention is to provide a prepreg, a film with resin, a metal foil with resin, a metal foil-clad laminate, and a wiring board obtained by using the resin composition.
[0012] One aspect of the present invention relates to a resin composition, which contains: a maleimide compound (A) having a benzene ring in the molecule and a maleimide equivalent of 500 g / mol or less; an imide compound (B) having at least one of a hydrocarbon group and a maleimide group at the end of the molecule; and a free radical polymerizable compound (C) having a benzene ring bonded to an alkenyl group in the molecule and a weight average molecular weight of 1000 or less.
[0013] The above and other objects, features and advantages of the present invention will become more apparent from the following detailed description and accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a schematic cross-sectional view showing an example of a prepreg according to an embodiment of the present invention.
[0015] Figure 2 This is a schematic cross-sectional view showing an example of a metal foil-clad laminate according to an embodiment of the present invention.
[0016] Figure 3 This is a schematic cross-sectional view showing an example of a wiring board according to an embodiment of the present invention.
[0017] Figure 4 This is a schematic cross-sectional view showing an example of a metal foil with resin according to an embodiment of the present invention.
[0018] Figure 5 This is a schematic cross-sectional view showing an example of a film with resin according to an embodiment of the present invention. DETAILED DESCRIPTION
[0019] The metal foil-clad laminate and the metal foil with resin used in manufacturing wiring boards etc. have not only an insulating layer but also a metal foil on the insulating layer. In addition, the wiring board also has not only an insulating layer but also wiring on the insulating layer. And as the wiring, wiring formed of metal foil etc. that the metal foil-clad laminate etc. have can be cited.
[0020] For the wiring boards used in various electronic devices, it is also required that they are not easily affected by changes in the external environment. For example, for the insulating layer of the wiring board, it is required that the changes in the relative dielectric constant and dielectric loss factor due to humidity changes are small, so that the wiring board can be used even in an environment with high humidity. Therefore, for the substrate material constituting the insulating layer of the wiring board, it is required that a cured product can be obtained in which the increase in the relative dielectric constant and dielectric loss factor due to moisture absorption is fully suppressed and the changes in the relative dielectric constant and dielectric loss factor due to humidity changes are small. More specifically, it is required that a cured product can be obtained in which the increase in the relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed.
[0021] The wiring board is also required to be less susceptible to the effects of reflow soldering during installation. For example, the insulating layer of the wiring board is required to be less susceptible to deformation due to the effects of reflow soldering, so that the wiring board can be used without problems even if the reflow soldering is performed. In other words, the insulating layer is required to be less susceptible to deformation due to temperature changes such as heating during the reflow soldering. In particular, as the semiconductor package substrate in the wiring board becomes thinner, there is a problem that poor installation is likely to occur due to warping of the semiconductor package on which the semiconductor chip is installed. In order to suppress the warping of the semiconductor package, the insulating layer is required to have a low thermal expansion coefficient. Therefore, the substrate material constituting the insulating layer of the wiring board is required to be able to obtain a cured product with a low thermal expansion coefficient.
[0022] Furthermore, in order to suppress the loss caused by the increase in resistance accompanying the miniaturization of wiring, the insulating layer provided in the wiring board is required to have a lower relative dielectric constant and dielectric loss tangent.
[0023] For these reasons, for substrate materials such as wiring boards, it is required to obtain a cured product having a low relative dielectric constant and dielectric loss tangent, in which the increase in the relative dielectric constant and dielectric loss tangent due to water absorption is fully suppressed, and which has a low thermal expansion coefficient, compared with the resin compositions described in Patent Documents 1 and 2.
[0024] The present inventors have conducted various studies and found that the above-mentioned object, i.e., providing a resin composition capable of obtaining a cured product having low relative dielectric constant and dielectric loss tangent, in which increases in relative dielectric constant and dielectric loss tangent due to water absorption are sufficiently suppressed, and in which a low thermal expansion coefficient is achieved by the following present invention.
[0025] Embodiments according to the present invention will be described below, but the present invention is not limited to these embodiments.
[0026] [Resin composition]
[0027] One embodiment of the present invention relates to a resin composition, which contains: a maleimide compound (A) having a benzene ring in the molecule and a maleimide equivalent of 500 g / mol or less; an imide compound (B) having at least one of a hydrocarbon group and a maleimide group at a molecular end; and a free radical polymerizable compound (C) having a benzene ring bonded to an alkenyl group in the molecule and a weight average molecular weight of 1000 or less. By curing the resin composition, a cured product having low relative dielectric constant and dielectric loss factor, and a sufficient suppression of the increase in relative dielectric constant and dielectric loss factor due to water absorption, and a low thermal expansion coefficient can be obtained.
[0028] (Maleimide compound (A))
[0029] The maleimide compound (A) is not particularly limited as long as it has a benzene ring in the molecule and has a maleimide equivalent of 500 g / mol or less. Examples of the maleimide compound (A) include solid maleimide compounds at 25°C.
[0030] The maleimide equivalent of the maleimide compound (A) is preferably 500 g / mol or less, more preferably 200 to 450 g / mol. If the maleimide equivalent is too low, the compatibility with the imide compound (B) is reduced, and there is a tendency to be easily separated from the resin composition when making a varnish. In addition, if the maleimide equivalent is too high, there is a tendency that the glass transition temperature of the obtained cured product is reduced and the thermal expansion coefficient becomes higher. Therefore, from the perspective of becoming a resin composition that can make a varnish with high uniformity and can obtain a cured product with a low thermal expansion coefficient, it is preferred that the maleimide equivalent of the maleimide compound (A) is within the above range. It should be noted that, here, the maleimide equivalent is the mass per 1 mol of maleimide group, for example, calculated by dividing the molecular weight of the maleimide compound by the number of maleimide groups, etc.
[0031] As the maleimide compound (A), for example, a maleimide compound having an arylene structure oriented and bonded at the meta position in the molecule can be listed. As the arylene structure oriented and bonded at the meta position, an arylene structure in which a structure containing a maleimide group is bonded to the meta position (an arylene structure in which a structure containing a maleimide group is substituted at the meta position) can be listed. The arylene structure oriented and bonded at the meta position is an arylene group oriented and bonded at the meta position such as a group shown in the following formula (2). As the arylene structure oriented and bonded at the meta position, for example, meta-phenylene and meta-naphthylene, etc. can be listed, and more specifically, a group shown in the following formula (2) can be listed.
[0032]
[0033] Examples of the maleimide compound (A) include a maleimide compound (A1) represented by the following formula (3), and more specifically, a maleimide compound (A2) represented by the following formula (4).
[0034]
[0035] In formula (3), Ar represents an arylene group that is oriented and bonded at the meta position. A , R B , R C and R D are independent of each other. That is, R A , R B , R c and R D They may be the same group or different groups. A , R B , R c and R D R represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a phenyl group, and is preferably a hydrogen atom. E and R F are independent of each other. That is, R E and R F They can be the same group or different groups. E and R F represents an aliphatic hydrocarbon group. s represents 1 to 5.
[0036] The arylene group is not particularly limited as long as it is an arylene group that is oriented and bonded at the meta position, and examples thereof include meta-arylene groups such as meta-phenylene and meta-naphthylene. More specifically, examples thereof include a group represented by the formula (2).
[0037] Examples of the alkyl group having 1 to 5 carbon atoms include methyl, ethyl, propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, pentyl, and neopentyl.
[0038] The aliphatic hydrocarbon group is a divalent group and may be acyclic or cyclic. Examples of the aliphatic hydrocarbon group include alkylene groups, and more specifically, methylene groups, methylmethylene groups, and dimethylmethylene groups. Among them, dimethylmethylene groups are preferred.
[0039] The maleimide compound (A1) represented by the formula (3) preferably has a repetition number s of 1 to 5. This s is an average value of the repetition number (polymerization degree).
[0040]
[0041] In the formula (4), s represents 1 to 5. This s is the same as s in the formula (3), and is the average value of the number of repetitions (polymerization degree).
[0042] The maleimide compound (A1) represented by the formula (3) and the maleimide compound (A2) represented by the formula (4) may contain a monofunctional compound in which s is 0, or a polyfunctional compound such as a heptafunctional compound or an octafunctional compound in which s is 6 or more, as long as the average value s of the number of repetitions (polymerization degree) is 1 to 5.
[0043] As the maleimide compound (A), a commercially available product may be used, and for example, the solid component of MIR-5000-60T manufactured by Nippon Kayaku Co., Ltd. may be used.
[0044] As described above, the maleimide compound (A) is not particularly limited as long as it has a benzene ring in the molecule and a maleimide compound with a maleimide equivalent of 500 g / mol or less. That is, the maleimide compound (A) can be a compound other than the exemplified maleimide compound, as long as it has a benzene ring in the molecule and a maleimide compound with a maleimide equivalent of 500 g / mol or less (other maleimide compounds). The other maleimide compounds are maleimide compounds with a benzene ring in the molecule and a maleimide equivalent of 500 g / mol or less, and examples thereof include: a monofunctional maleimide compound with one maleimide group in the molecule, a polyfunctional maleimide compound with more than two maleimide groups in the molecule, and a modified maleimide compound, etc. As the modified maleimide compound, for example, a modified maleimide compound in which a part of the molecule is modified by an amine compound, a modified maleimide compound in which a part of the molecule is modified by an organosilicon compound, and a modified maleimide compound in which a part of the molecule is modified by an amine compound and an organosilicon compound. In addition, as the maleimide compound (A), the exemplified maleimide compound can be used alone, or two or more thereof can be used in combination. For example, as the maleimide compound (A), the maleimide compound (A1) shown in formula (3) can be used alone, or two or more maleimide compounds (A1) shown in formula (3) can be used in combination. In the case of using two or more maleimide compounds (A1) shown in formula (3) in combination, for example, the case of using a maleimide compound (A1) shown in formula (3) other than the maleimide compound (A2) shown in formula (4) and a maleimide compound (A2) shown in formula (4) in combination can be mentioned.
[0045] (Imide compound (B))
[0046] The imide compound (B) is a compound different from the maleimide compound (A), and is not particularly limited as long as it is an imide compound having at least one of a hydrocarbon group and a maleimide group at a molecular end. Examples of the imide compound (B) include, for example, an imide compound having a structure represented by the following formula (1) in the molecule.
[0047]
[0048] In formula (1), X1 represents a tetravalent tetracarboxylic acid residue. X2 represents a divalent aliphatic diamine residue. X3 represents a divalent aromatic diamine residue. X4 and X5 are each independent. That is, X4 and X5 may be the same group or different groups. In addition, X4 and X5 represent a hydrocarbon group having 1 to 20 carbon atoms, a maleimide group or an anhydride group, and at least one of X4 and X5 represents a hydrocarbon group having 1 to 20 carbon atoms or a maleimide group. m represents 1 to 50, n represents 0 to 49, and the sum of m and n represents 1 to 50. The imide compound (B) as shown in the formula (1) contains the aliphatic diamine residue in the molecule, and may also contain the aromatic diamine residue in the molecule. In addition, the imide compound (B) may also be a random copolymer in which repeating units containing the aliphatic diamine residue and repeating units containing the aromatic diamine residue are randomly present.
[0049] The tetracarboxylic acid residue is not particularly limited as long as it is a tetravalent group derived from tetracarboxylic acid or tetracarboxylic dianhydride. Examples of the tetracarboxylic acid residue include, for example, a residue obtained by removing four carboxyl groups from tetracarboxylic acid, or a residue obtained by removing an acid dianhydride structure from tetracarboxylic dianhydride. Examples of the tetracarboxylic acid residue include, for example, a tetravalent tetracarboxylic acid residue having 2 to 40 carbon atoms.
[0050] The aliphatic diamine residue is not particularly limited as long as it is a divalent group derived from an aliphatic diamine compound. Examples of the aliphatic diamine residue include a residue obtained by removing two amino groups from an aliphatic diamine compound. In addition, the aromatic diamine residue is not particularly limited as long as it is a divalent group derived from an aromatic diamine compound. Examples of the aromatic diamine residue include a residue obtained by removing two amino groups from an aromatic diamine compound.
[0051] The hydrocarbon group is not particularly limited as long as it is a hydrocarbon group having 1 to 20 carbon atoms. The acid anhydride group is not particularly limited. Examples of the acid anhydride group include an acid anhydride group contained in tetracarboxylic dianhydride that constitutes the tetracarboxylic acid residue (which is a raw material for the imide compound (B)).
[0052] As described above, the imide compound (B) is an imide compound having at least one of a hydrocarbon group and a maleimide group at the molecular end. That is, the imide compound (B) is a compound in which, in the structure represented by the formula (1), X4 and X5 each independently represent a hydrocarbon group having 1 to 20 carbon atoms, a maleimide group or an anhydride group, and at least one of X4 and X5 represents a hydrocarbon group having 1 to 20 carbon atoms or a maleimide group. Examples of the imide compound (B) include an imide compound (B-1) in which at least one of X4 and X5 is a hydrocarbon group having 1 to 20 carbon atoms, and an imide compound (B-2) in which at least one of X4 and X5 is a maleimide group.
[0053] m and n in the imide compound (B-1) are average values of the number of repeating units (polymerization degree), and for example, the sum of m and n can be listed as the number of repeating units that become the following acid value or the following weight average molecular weight. In addition, the sum of m and n is preferably 1 to 50, for example. In addition, the ratio of m to the sum of m and n [m / (m+n)] is preferably 0 or more and 0.98 or less [0≤m / (m+n)≤0.98], more preferably 0 or more and 0.5 or less [0≤m / (m+n)≤0.5], and further preferably 0 or more and 0.4 or less [0≤m / (m+n)≤0.4]. It should be noted that the ratio of m to the sum of m and n [m / (m+n)] represents the proportion of the aliphatic amine residue in the sum of the aliphatic diamine residue and the aromatic diamine residue.
[0054] The m and n in the imide compound (B-2) are average values of the number of repeating units (polymerization degree), and for example, the sum of m and n can be listed as the number of repeating units that become the following acid value or the following weight average molecular weight. In addition, the sum of m and n is preferably, for example, 1 to 50, and more preferably 1 to 15. In addition, the ratio of m to the sum of m and n [m / (m+n)] is preferably 0 or more and 0.98 or less [0≤m / (m+n)≤0.98], more preferably 0 or more and 0.5 or less [0≤m / (m+n)≤0.5], and further preferably 0 or more and 0.4 or less [0≤m / (m+n)≤0.4].
[0055] The acid value of the imide compound (B-1) is preferably 0 to 20 mgKOH / g, more preferably 0 to 15 mgKOH / g. If the acid value is too high, the compatibility with the maleimide compound (A) increases, the glass transition temperature of the obtained cured product tends to decrease, and the thermal expansion coefficient tends to increase.
[0056] The acid value herein refers to the acid value per 1 g of the imide compound (B-1). The acid value can be measured by a potentiometric titration method in accordance with DIN EN ISO 2114.
[0057] The weight average molecular weight of the imide compound (B-1) is preferably 10000 to 30000, more preferably 10000 to 20000. If the weight average molecular weight is too low, the resin viscosity decreases, and there is a tendency for the resin flow during press molding to become too large. In addition, if the weight average molecular weight is too high, the resin viscosity increases, and there is a tendency for the resin flow during press molding to become too small or the compatibility with the maleimide compound (A) to decrease. If the resin flow becomes too small, there is a risk of, for example, reduced circuit filling. In addition, if the compatibility with the maleimide compound (A) is excessively reduced, the dispersion state in the cured product deteriorates, and there is a risk that the maleimide compound (A) and the imide compound (B-1) become uneven. Therefore, from the viewpoint of moldability and compatibility, it is preferred that the weight average molecular weight of the imide compound (B-1) is within the above range.
[0058] The weight average molecular weight of the imide compound (B-2) is preferably 600 to 5000, more preferably 1000 to 4000. If the weight average molecular weight is too low, the resin viscosity decreases, and there is a tendency for the resin flow during press molding to become too large. In addition, if the weight average molecular weight is too high, the resin viscosity increases, and there is a tendency for the resin flow during press molding to become too small or the compatibility with the maleimide compound (A) to decrease. If the resin flow becomes too small, there is a risk of, for example, reduced circuit filling. In addition, if the compatibility with the maleimide compound (A) is excessively reduced, the dispersion state in the cured product deteriorates, and there is a risk that the maleimide compound (A) and the imide compound (B-2) become uneven. Therefore, from the viewpoint of moldability and compatibility, it is preferred that the weight average molecular weight of the imide compound (B-2) is within the above range.
[0059] In addition, here, the weight average molecular weight may be a value measured by a common molecular weight measurement method, and specifically, a value measured using gel permeation chromatography (GPC) and the like are mentioned.
[0060] The imide compound (B) [the imide compound (B-1) and the imide compound (B-2)] preferably contains 2 to 4 mmol / g of an imide group. If the amount of the imide group is too small, there is a tendency that the glass transition temperature of the obtained cured product is lowered and the thermal expansion coefficient is lowered. In addition, if the amount of the imide group is too much, the compatibility with the maleimide compound (A) is reduced, and there is a tendency that the maleimide compound (A) and the imide compound (B) in the cured product become uneven. Therefore, from the perspective of producing a uniform cured product and a resin composition that can obtain a cured product with a low thermal expansion coefficient, it is preferred that the amount of the imide group is within the above range.
[0061] As the imide compound (B), as long as it contains an imide compound having the structure represented by the formula (1) in the molecule, other imide compounds may be contained.
[0062] (Radical polymerizable compound (C))
[0063] The free radical polymerizable compound (C) is a compound different from the maleimide compound (A) and the imide compound (B), and is not particularly limited as long as it has a benzene ring bonded to an alkenyl group in the molecule and a free radical polymerizable compound with a weight average molecular weight of less than 1000. The alkenyl group can be listed as allyl, vinyl and propenyl, etc. That is, as the free radical polymerizable compound (C), for example, a benzene ring bonded to at least one selected from the group consisting of allyl, vinyl and propenyl groups in the molecule and a free radical polymerizable compound with a weight average molecular weight of less than 1000 can be listed. It should be noted that, as described above, the free radical polymerizable compound (C) is a compound that is different from both the maleimide compound (A) and the imide compound (B). That is, in the resin composition, the maleimide compound (A), the imide compound (B) and the free radical polymerizable compound (C) are different from each other.
[0064] The weight average molecular weight of the free radical polymerizable compound (C) is preferably 1000 or less, more preferably 110 to 600. If the weight average molecular weight is too low, there is a tendency that the glass transition temperature of the obtained cured product is reduced and the thermal expansion coefficient is reduced. In addition, if the weight average molecular weight is too high, there is also a tendency that the glass transition temperature of the obtained cured product is reduced and the thermal expansion coefficient is reduced. It should be noted that, here, the weight average molecular weight can be any value obtained by measuring the molecular weight using a conventional molecular weight measurement method, and specifically, the value measured using gel permeation chromatography (GPC) can be cited.
[0065] Examples of the radical polymerizable compound (C) include benzoxazine compounds (C-1) having a benzene ring bonded to an alkenyl group in the molecule and hydrocarbon compounds (C-2) having a benzene ring bonded to an alkenyl group in the molecule.
[0066] The oxazine compound (C-1) is not particularly limited as long as it is an oxazine compound having a benzene ring bonded to an alkenyl group in the molecule. Examples of the benzoxazinyl group include, for example, a benzoxazinyl group represented by the following formula (5). In addition, examples of the benzoxazine compound (C-1) include a benzoxazine compound (C-1-1) having a benzoxazinyl group represented by the following formula (5) in the molecule.
[0067]
[0068] In formula (5), R1 represents an allyl group, and p represents 1 to 4. p is the average value of the degree of substitution of R1, and is 1 to 4, preferably 1.
[0069] As the oxazine compound (C-1), specifically, as the benzoxazine compound (C-1-1), there can be mentioned a benzoxazine compound (C-1·2) represented by the following formula (6). As the benzoxazine compound (C-1), it is preferred that the benzoxazine compound (C-1-2) is included.
[0070]
[0071] In formula (6), R2 and R3 represent allyl groups, X6 represents an alkylene group, and q and r each independently represent 1 to 4. That is, q and r may be the same or different, and each represent 1 to 4.
[0072] The alkylene group is not particularly limited, and examples thereof include methylene, ethenyl, propenyl, butenyl, pentenyl, hexenyl, heptenyl, octyl, eicosyl, and hexatriacontyl groups, among which methylene is preferred.
[0073] q is the average value of the degree of substitution of R2, and is 1 to 4, preferably 1. Moreover, r is the average value of the degree of substitution of R3, and is 1 to 4, preferably 1.
[0074] The oxazine compound (C-1) may include oxazine compounds (other oxazine compounds) other than the benzoxazine compound (C-1-1) (the benzoxazine compound (C-1-2) etc.) as long as it is an oxazine compound having an oxazine group in the molecule. Examples of the other oxazine compounds include benzoxazine compounds having a phenolphthalein structure in the molecule (phenolphthalein type benzoxazine compounds), bisphenol F type benzoxazine compounds, and diaminodiphenylmethane (DDM) type benzoxazine compounds. More specifically, examples of the other oxazine compounds include 3,3'·(methylene-1,4-diphenylene)bis(3,4-dihydro-2H-1,3-benzoxazine) (Pd type benzoxazine compound), and 2,2-bis(3,4-dihydro-2H-3-phenyl-1,3-benzoxazine)methane (Fa type benzoxazine compound).
[0075] As the benzoxazine compound (C-1), a commercially available product may be used, and for example, ALPd manufactured by Shikoku Chemicals Co., Ltd. may be used.
[0076] As the benzoxazine compound (C-1), the benzoxazine compounds exemplified above may be used alone or in combination of two or more.
[0077] The hydrocarbon compound (C-2) is not particularly limited as long as it is a hydrocarbon compound having a benzene ring bonded to an alkenyl group in the molecule. Examples of the hydrocarbon compound (C-2) include divinylbenzenes such as o-divinylbenzene, m-divinylbenzene and p-divinylbenzene, hydrocarbon compounds represented by the following formula (7), and hydrocarbon compounds represented by the following formula (9).
[0078]
[0079] In formula (7), Y represents a hydrocarbon group containing at least one selected from aromatic ring groups and aliphatic ring groups and having 6 or more carbon atoms. a represents 1 to 10.
[0080] The aromatic ring group is not particularly limited, and examples thereof include phenylene group, xylylene group, naphthylene group, tolylene group, and biphenylene group. The aliphatic ring group is not particularly limited, and examples thereof include groups containing indane structures and groups containing cycloolefin structures. Among them, Y is preferably the aromatic ring group, and more preferably a xylylene group. The carbon number of the hydrocarbon group is not particularly limited as long as it is 6 or more, and is preferably 6 to 20. As the hydrocarbon compound (C-2) [hydrocarbon compound represented by formula (7)], more specifically, hydrocarbon compounds represented by the following formula (8) and the like can be listed. In addition, the hydrocarbon compound (C-2) preferably includes a hydrocarbon compound represented by the following formula (8).
[0081]
[0082] In the formula (8), a represents 1 to 10.
[0083]
[0084] In formula (9), b represents 0 to 20.
[0085] In the compound represented by the formula (9), b is 0 to 20, preferably 1 to 20, more preferably 1 to 12, and even more preferably 1 to 6. Specific examples of the compound represented by the formula (9) include the compound represented by the formula (9) wherein b is 1 [bis(4-vinylphenyl)methane (BVPM)], the compound represented by the formula (9) wherein b is 2 [1,2-bis(vinylphenyl)ethane (BVPE)], and the compound represented by the formula (9) wherein b is 6 [1,6-bis(4-vinylphenyl)hexane (BVPH)].
[0086] As the radical polymerizable compound (C), the radical polymerizable compounds exemplified above may be used alone or in combination of two or more.
[0087] (Inorganic filler)
[0088] As required, the resin composition may contain an inorganic filler within the range that does not impair the effect of the present invention. In addition, from the viewpoint of being able to improve the heat resistance of the cured product of the resin composition, it is preferred to contain the inorganic filler. The inorganic filler is not particularly limited as long as it is an inorganic filler that can be used as an inorganic filler contained in the resin composition. As the inorganic filler, for example: metal oxides such as silicon dioxide, aluminum oxide, titanium oxide, magnesium oxide and mica, metal hydroxides such as magnesium hydroxide and aluminum hydroxide, talc, aluminum borate, barium sulfate, aluminum nitride, boron nitride, barium titanate, strontium titanate, calcium titanate, aluminum titanate, magnesium carbonate such as anhydrous magnesium carbonate, and calcium carbonate, etc. can be cited. Among them, preferred are metal hydroxides such as silicon dioxide, magnesium hydroxide and aluminum hydroxide, aluminum oxide, boron nitride, strontium titanate and calcium titanate, etc., and more preferably silicon dioxide. The silicon dioxide is not particularly limited, and for example, crushed silicon dioxide, spherical silicon dioxide, and silicon dioxide particles can be cited, preferably spherical silicon dioxide.
[0089] The inorganic filler may be a surface-treated inorganic filler or an untreated inorganic filler. Examples of the surface treatment include treatment with a silane coupling agent.
[0090] The silane coupling agent is not particularly limited, and examples thereof include silane coupling agents having at least one functional group selected from the group consisting of vinyl, styryl, methacryl, acryl, phenylamino, isocyanurate, urea, mercapto, isocyanate, epoxy, and anhydride groups. That is, examples of the silane coupling agent include compounds having at least one of vinyl, styryl, methacryl, acryl, phenylamino, isocyanurate, urea, mercapto, isocyanate, epoxy, and anhydride groups as reactive functional groups and having hydrolyzable groups such as methoxy or ethoxy groups.
[0091] Regarding the silane coupling agent, as a silane coupling agent having a vinyl group, for example, vinyl triethoxysilane and vinyl trimethoxysilane can be listed. Regarding the silane coupling agent, as a silane coupling agent having a styrene group, for example, p-styrene trimethoxysilane and p-styrene triethoxysilane can be listed. Regarding the silane coupling agent, as a silane coupling agent having a methacryloyl group, for example, 3-methacryloyloxypropyl trimethoxysilane, 3-methacryloyloxypropyl methyl dimethoxysilane, 3-methacryloyloxypropyl triethoxysilane, 3-methacryloyloxypropyl methyl diethoxysilane, and 3-methacryloyloxypropyl ethyl diethoxysilane can be listed. Regarding the silane coupling agent, as a silane coupling agent having an acryl group, for example, 3-acryloyloxypropyl trimethoxysilane and 3-acryloyloxypropyl triethoxysilane can be listed. As for the silane coupling agent, examples of the silane coupling agent having a phenylamino group include N-phenyl-3-aminopropyltrimethoxysilane and N-phenyl-3-aminopropyltriethoxysilane.
[0092] The average particle size of the inorganic filler is not particularly limited, and is preferably 0.05 to 10 μm, and more preferably 0.1 to 8 μm. It should be noted that the lower average particle size here refers to the volume average particle size. The volume average particle size can be measured by, for example, laser diffraction method.
[0093] (content)
[0094] The content of the maleimide compound (A) is preferably 30 to 70 parts by mass, more preferably 35 to 65 parts by mass, based on 100 parts by mass of the total of the maleimide compound (A), the imide compound (B) and the radical polymerizable compound (C).
[0095] The content of the imide compound (B) is preferably 5 to 40 parts by mass, more preferably 10 to 35 parts by mass, based on 100 parts by mass of the total of the maleimide compound (A), the imide compound (B) and the radical polymerizable compound (C).
[0096] The content of the radical polymerizable compound (C) is preferably 5 to 40 parts by mass, more preferably 10 to 30 parts by mass, based on 100 parts by mass of the total of the maleimide compound (A), the imide compound (B) and the radical polymerizable compound (C).
[0097] If the contents of the maleimide compound (A), the imide compound (B) and the radical polymerizable compound (C) are within the above ranges, a resin composition having a low relative dielectric constant and a low dielectric loss factor, in which the increase in the relative dielectric constant and the dielectric loss factor due to water absorption is fully suppressed, and a cured product having a low thermal expansion coefficient can be obtained more suitably. This is because if the contents of the maleimide compound (A), the imide compound (B) and the radical polymerizable compound (C) are within the above ranges, the effects of containing the maleimide compound (A), the effects of containing the imide compound (B), and the effects of containing the radical polymerizable compound (B) can be fully exerted, respectively.
[0098] (Styrene polymer)
[0099] The resin composition may also contain a styrene polymer. The styrene polymer is a polymer obtained by, for example, polymerizing a monomer containing a styrene monomer, and may be a styrene copolymer. In addition, as the styrene copolymer, for example, a copolymer obtained by copolymerizing one or more styrene monomers and one or more other monomers copolymerizable with the styrene monomer may be cited. As long as the styrene copolymer has a structure derived from the styrene monomer in the molecule, it may be a random copolymer or a block copolymer. As the block copolymer, there may be cited: a binary copolymer of a structure (repeating unit) derived from the styrene monomer and the other monomers (repeating units) that can be copolymerized; a ternary copolymer of a structure (repeating unit) derived from the styrene monomer, the other monomers (repeating units) that can be copolymerized, and a structure (repeating unit) derived from the styrene monomer; and a ternary copolymer of a structure (repeating unit) derived from the styrene monomer, a random copolymerization block (repeating unit) containing the other monomers that can be copolymerized and the styrene monomer, and a structure (repeating unit) derived from the styrene monomer. The styrene polymer may also be a hydrogenated styrene copolymer obtained by hydrogenating at least a portion of the styrene copolymer. More specifically, the styrene polymer includes methyl styrene (ethylene / butylene) methyl styrene block copolymer, methyl styrene (ethylene-ethylene / propylene) methyl styrene block copolymer, styrene-isoprene block copolymer, hydrogenated styrene-isoprene-styrene block copolymer, styrene (ethylene / butylene) styrene block copolymer, styrene (ethylene-ethylene / propylene) styrene block copolymer, methyl styrene (styrene / butadiene random copolymerization block) methyl styrene copolymer, styrene (styrene diene random copolymerization block) styrene copolymer, and hydrogenated products thereof in which at least a portion of the styrene copolymer is hydrogenated.
[0100] (Organic ingredients)
[0101] The resin composition involved in the present embodiment may also contain organic components other than the maleimide compound (A), the imide compound (B), the radical polymerizable compound (C) and the styrene polymer as required within the scope of not damaging the effect of the present invention. Here, the organic component may react with at least one of the maleimide compound (A), the imide compound (B) and the radical polymerizable compound (C), or may not react. As the organic component, for example, epoxy compounds, methacrylate compounds, acrylate compounds, vinyl compounds, cyanate compounds, active ester compounds, and allyl compounds may be listed.
[0102] The epoxy compound is a compound having an epoxy group in the molecule, and specifically includes: bisphenol-type epoxy compounds such as bisphenol A epoxy compounds, phenol novolac-type epoxy compounds, cresol novolac-type epoxy compounds, dicyclopentadiene-type epoxy compounds, bisphenol A novolac-type epoxy compounds, biphenyl aralkyl-type epoxy compounds, polybutadiene compounds having an epoxy group in the molecule, and epoxy compounds containing a naphthalene ring, etc. In addition, the epoxy compound also includes epoxy resins which are polymers of the epoxy compounds.
[0103] The methacrylate compound is a compound having a methacryloyl group in the molecule, and examples thereof include a monofunctional methacrylate compound having one methacryloyl group in the molecule and a polyfunctional methacrylate compound having two or more methacryloyl groups in the molecule. Examples of the monofunctional methacrylate compound include methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate. Examples of the polyfunctional methacrylate compound include dimethacrylate compounds such as tricyclodecane dimethanol dimethacrylate (DCP).
[0104] The acrylate compound is a compound having an acryloyl group in the molecule, and examples thereof include a monofunctional acrylate compound having one acryloyl group in the molecule and a multifunctional acrylate compound having two or more acryloyl groups in the molecule. Examples of the monofunctional acrylate compound include methyl acrylate, ethyl acrylate, propyl acrylate, and butyl acrylate. Examples of the multifunctional acrylate compound include diacrylate compounds such as tricyclodecane dimethanol diacrylate.
[0105] The vinyl compound is a compound having a vinyl group in the molecule, and examples thereof include: a monofunctional vinyl compound (monovinyl compound) having one vinyl group in the molecule, and a polyfunctional vinyl compound having two or more vinyl groups in the molecule. Examples of the polyfunctional vinyl compound include: divinylbenzene, a curable polybutadiene having a carbon-carbon unsaturated double bond in the molecule, a butadiene-styrene copolymer other than the styrene polymer, a polyphenylene ether compound having a vinylbenzyl group (vinylbenzyl) at the end, and a modified polyphenylene ether in which the terminal hydroxyl group of the polyphenylene ether is modified with a methacryloyl group. In addition, examples thereof include: a curable butadiene-styrene copolymer having a carbon-carbon unsaturated double bond in the molecule which is liquid at 25°C, a curable butadiene-styrene random copolymer having a carbon-carbon unsaturated double bond in the molecule which is liquid at 25°C, and a curable butadiene-styrene random copolymer having a carbon-carbon unsaturated double bond in the molecule which is liquid at 25°C.
[0106] The cyanate compound is a compound having a cyano group in the molecule, and examples thereof include 2,2-bis(4-cyanatophenyl)propane, bis(3,5-dimethyl-4-cyanatophenyl)methane, and 2,2-bis(4-cyanatophenyl)ethane.
[0107] The active ester compound is a compound having an ester group with high reactivity in the molecule, and examples thereof include benzenecarboxylic acid active ester, benzenedicarboxylic acid active ester, benzenetricarboxylic acid active ester, benzenetetracarboxylic acid active ester, naphthalenecarboxylic acid active ester, naphthalenedicarboxylic acid active ester, naphthalenetricarboxylic acid active ester, naphthalenetetracarboxylic acid active ester, fluorenecarboxylic acid active ester, fluorenedicarboxylic acid active ester, fluorenetricarboxylic acid active ester, and fluorenetetracarboxylic acid active ester. ester) etc.
[0108] The allyl compound is a compound having an allyl group in the molecule, and examples thereof include triallyl isocyanurate compounds such as triallyl isocyanurate (TAIC), diallyl bisphenol compounds, and diallyl phthalate (DAP).
[0109] The organic components may be used alone or in combination of two or more.
[0110] The weight average molecular weight of the organic component is not particularly limited, for example, preferably 100 to 5000, more preferably 100 to 4000, and further preferably 100 to 3000. If the weight average molecular weight of the organic component is too low, there is a risk that the organic component is easily volatilized from the compounding component system of the resin composition. In addition, if the weight average molecular weight of the organic component is too high, the viscosity of the varnish of the resin composition and the melt viscosity during heat forming become too high, thereby causing the appearance to deteriorate and the formability to deteriorate when the B stage is made. Therefore, if the weight average molecular weight of the organic component is within this range, a resin composition with better heat resistance and formability of the cured product can be obtained. It is believed that this is because the resin composition can be cured well. It should be noted that, here, the weight average molecular weight is as long as the value obtained by measuring the molecular weight by a conventional molecular weight measurement method, and specifically, the value measured using gel permeation chromatography (GPC) can be cited.
[0111] Regarding the organic component, the average number of functional groups (number of functional groups) in each molecule of the organic component that contributes to the reaction when the resin composition is cured varies according to the weight average molecular weight of the organic component, and is preferably 1 to 20, and more preferably 2 to 18. If the number of functional groups is too small, there is a tendency that it is difficult to obtain a cured product with sufficient heat resistance. In addition, if the number of functional groups is too large, the reactivity becomes too high, and there is a risk of adverse conditions such as reduced storage of the resin composition or reduced fluidity of the resin composition.
[0112] (Other ingredients)
[0113] The resin composition may contain ingredients (other ingredients) other than the maleimide compound (A), the imide compound (B) and the free radical polymerizable compound (C) within the scope of not impairing the effect of the present invention. The resin composition may also contain the styrene polymer, the inorganic filler and the organic component as the other ingredients as described above. As the other ingredients, in addition to the styrene polymer, the inorganic filler and the organic component, additives such as flame retardants, reaction initiators, curing accelerators, catalysts, polymerization retarders, polymerization inhibitors, dispersants, leveling agents, coupling agents, defoamers, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, dyes or pigments, and lubricants may be cited.
[0114] As described above, the resin composition involved in the present embodiment may contain a flame retardant. By containing a flame retardant, the flame retardancy of the cured product of the resin composition can be improved. The flame retardant is not particularly limited. Specifically, in the field of using halogen flame retardants such as brominated flame retardants, preferred are, for example: ethylenedipentabromobenzene (ethylenedipentabromobenzene), ethylenebistetrabromoimide (ethylenebistetrabromoimide), decabromodiphenyl ether, tetradecabromodiphenoxybenzene, and bromostyrene compounds reacting with the polymerizable compound having a melting point of more than 300°C. It is believed that by using a halogen flame retardant, the detachment of halogen at high temperature can be suppressed, and the reduction of heat resistance can be suppressed. In addition, in the field requiring halogen-free, phosphorus-containing flame retardants (phosphorus-based flame retardants) are sometimes used. The phosphorus-based flame retardant is not particularly limited, and examples thereof include: phosphate ester-based flame retardant, phosphazene-based flame retardant, bisdiphenylphosphine-based flame retardant, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) flame retardant, and phosphinate-based flame retardant. As a specific example of phosphate ester flame retardant, condensation phosphate of dixylyl phosphate can be listed. As a specific example of phosphazene flame retardant, phenoxyphosphazene can be listed. As a specific example of bisdiphenylphosphine-based flame retardant, xylene bis(diphenylphosphine oxide) can be listed. As a specific example of DOPO flame retardant, for example, hydrocarbons (DOPO derivative compounds) having two DOPO groups in the molecule and DOPO having a reactive functional group can be listed. Specific examples of the hypophosphite-based flame retardant include metal hypophosphite of dialkyl aluminum hypophosphite. As the flame retardant, each of the exemplified flame retardants may be used alone or in combination of two or more.
[0115] As described above, the resin composition involved in the present embodiment may contain a reaction initiator. As long as the reaction initiator can promote the curing reaction of the resin composition, it is not particularly limited, and examples thereof include peroxides and organic azo compounds. As the peroxide, examples thereof include: α, α'-di(tert-butylperoxy)diisopropylbenzene (PBP), 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, and benzoyl peroxide, etc. In addition, as the organic azo compound, examples thereof include azobisisobutyronitrile, etc. In addition, carboxylic acid metal salts, etc., may be used in combination as needed. Accordingly, the curing reaction may be further promoted. Among them, α, α'-di(tert-butylperoxy)diisopropylbenzene is preferably used. α, α'-di(tert-butylperoxy)diisopropylbenzene has a relatively high reaction starting temperature, so it can inhibit the promotion of the curing reaction at the moment when the prepreg is dried and curing is not required, and the preservation property of the resin composition may be inhibited from decreasing. Furthermore, α,α'-di(tert-butylperoxy)diisopropylbenzene has low volatility and therefore does not volatilize during drying and storage of the prepreg, and has good stability. The reaction initiator may be used alone or in combination of two or more.
[0116] As described above, the resin composition involved in the present embodiment may contain a curing accelerator. The curing accelerator is not particularly limited as long as it can promote the curing reaction of the resin composition. As the curing accelerator, specifically, amines such as imidazoles and their derivatives, organic phosphine compounds, secondary amines and tertiary amines, quaternary ammonium salts, organic boron compounds, and metal soaps can be cited. As the imidazoles, for example, 2-ethyl-4-methylimidazole (2E4MZ), 2-methylimidazole, 2-phenyl-4-methylimidazole, 2-phenylimidazole, and 1-benzyl-2-methylimidazole can be cited. In addition, as the organic phosphine compounds, triphenylphosphine, diphenylphosphine, phenylphosphine, tributylphosphine and trimethylphosphine can be cited. In addition, as the amines, for example, dimethylbenzylamine, triethylenediamine, triethanolamine, 1,8-diazabicyclo (5,4,0) undecene-7 (DBU) can be cited. In addition, as the quaternary ammonium salts, tetrabutylammonium bromide can be cited. In addition, examples of the organic boron compound include tetraphenyl borate salts such as 2-ethyl-4-methylimidazoletetraphenylborate, and tetrasubstituted phosphonium tetrasubstituted borate salts such as tetraphenylphosphonium ethyltriphenylborate. In addition, the metal soap refers to a fatty acid metal salt, which may be a linear fatty acid metal salt or a cyclic fatty acid metal salt. Specifically, examples of the metal soap include linear aliphatic metal salts and cyclic aliphatic metal salts having 6 to 10 carbon atoms. More specifically, examples include aliphatic metal salts formed by linear fatty acids such as stearic acid, lauric acid, ricinoleic acid, and octanoic acid, or cyclic fatty acids such as cyclopentane acid, and metals such as lithium, magnesium, calcium, barium, copper, and zinc. For example, zinc octanoate may be cited. The curing accelerators may be used alone or in combination of two or more.
[0117] As described above, the resin composition involved in the present embodiment may contain a silane coupling agent. The silane coupling agent may be contained in the resin composition, or may be contained in the form of a silane coupling agent that has been pre-surface treated for the inorganic filler contained in the resin composition. Wherein, as the silane coupling agent, it is preferably contained in the form of a silane coupling agent that has been pre-surface treated for the inorganic filler, and more preferably, it is contained in the form of a silane coupling agent that has been pre-surface treated for the inorganic filler, and the resin composition also contains a silane coupling agent. In addition, with respect to prepreg, it may be contained in the form of a silane coupling agent that has been pre-surface treated for a fibrous substrate in the prepreg. As the silane coupling agent, for example, the silane coupling agent identical to the silane coupling agent used when the inorganic filler is surface treated as described above may be cited.
[0118] The resin composition according to the present embodiment is a resin composition capable of obtaining a cured product having low relative dielectric constant and dielectric loss tangent, in which increases in relative dielectric constant and dielectric loss tangent due to water absorption are sufficiently suppressed, and having a low thermal expansion coefficient.
[0119] (use)
[0120] As described later, the resin composition is used when manufacturing a prepreg. In addition, the resin composition is used when forming a resin layer provided on a metal foil with a resin and a film with a resin, and an insulating layer provided on a metal foil-clad laminate and a wiring board.
[0121] (Manufacturing method)
[0122] The method for manufacturing the resin composition is not particularly limited, and examples thereof include: a method of mixing the maleimide compound (A), the imide compound (B), the radical polymerizable compound (C), and components other than the maleimide compound (A), the imide compound (B), and the radical polymerizable compound (C) added as needed under conditions of a specified content, etc. In addition, in the case of obtaining a varnish-like composition containing an organic solvent, the method described below, etc., can be cited.
[0123] By using the resin composition according to the present embodiment, a prepreg, a metal foil-clad laminate, a wiring board, a metal foil with a resin, and a film with a resin can be obtained as described below.
[0124] [Prepreg]
[0125] Figure 1 This is a schematic cross-sectional view showing an example of the prepreg 1 according to the embodiment of the present invention.
[0126] like Figure 1As shown, the prepreg 1 according to the present embodiment comprises: the resin composition or the semi-cured product 2 of the resin composition; and a fibrous base material 3. The prepreg 1 comprises: the resin composition or the semi-cured product 2 of the resin composition; and the fibrous base material 3 present in the resin composition or the semi-cured product 2 of the resin composition.
[0127] It should be noted that, in the present embodiment, semi-cured material is a material that cures the resin combination to a state that can further be cured midway. That is, semi-cured material is a material that makes the state (B-stage) of the resin combination semi-cured. For example, if the resin combination is heated, the initial viscosity is slowly reduced, and then begins to solidify, and the viscosity slowly rises. In this case, as semi-cured, the state during the period from when the viscosity begins to rise to before fully solidified, etc. can be cited.
[0128] As the prepreg obtained by using the resin composition involved in the present embodiment, it can be a prepreg with a semi-cured product of the resin composition as described above, and it can also be a prepreg with an uncured resin composition. That is, it can be a prepreg with a semi-cured product of the resin composition (the resin composition in the B stage) and a fibrous substrate, and it can also be a prepreg with the resin composition before curing (the resin composition in the A stage) and a fibrous substrate. In addition, as the resin composition or the semi-cured product of the resin composition, it can be a substance obtained by drying or heat-drying the resin composition.
[0129] When manufacturing the prepreg, the resin composition 2 is often used in a varnish state in order to be impregnated into the substrate for forming the prepreg, i.e., the fibrous substrate 3. That is, the resin composition 2 is usually often a resin varnish prepared in a varnish state. The varnish-like resin composition (resin varnish) can be prepared, for example, in the following manner.
[0130] First, each component soluble in an organic solvent is put into an organic solvent and dissolved. At this time, heating can be performed as needed. Then, a component insoluble in an organic solvent used as needed is added, and a ball mill, a bead mill, a planetary mixer, a roller mill, etc. are used to disperse it to a specified dispersed state, thereby a varnish-like resin composition can be modulated. As the organic solvent used herein, as long as it is an organic solvent that can dissolve the maleimide compound (A), the imide compound (B) and the free radical polymerizable compound (C) and the like and does not hinder the curing reaction, it is not particularly limited. Specifically, for example, toluene, methyl ethyl ketone (MEK) etc. can be cited.
[0131] As the fibrous substrate, specifically, for example, glass cloth, aramid cloth, polyester cloth, glass nonwoven fabric, aramid nonwoven fabric, polyester nonwoven fabric, pulp paper and cotton linter paper can be cited. It should be noted that if glass cloth is used, a laminate with excellent mechanical strength can be obtained, and glass cloth processed by flattening is particularly preferred. As the flattening process, specifically, for example, a method in which the yarn is compressed into a flat state by continuously pressing the glass cloth with a pressing roller at an appropriate pressure. It should be noted that the thickness of the commonly used fibrous substrate is, for example, greater than 0.01 mm and less than 0.3 mm. In addition, the glass fiber constituting the glass cloth is not particularly limited, and for example, Q glass, NE glass, E glass, S glass, T glass, L glass and L2 glass can be cited. In addition, the surface of the fibrous substrate can be surface treated with a silane coupling agent. The silane coupling agent is not particularly limited, and examples thereof include silane coupling agents having at least one group selected from the group consisting of a vinyl group, an acryloyl group, a methacryloyl group, a styryl group, an amino group, and an epoxy group in the molecule.
[0132] The method for producing the prepreg is not particularly limited as long as the prepreg can be produced. Specifically, when producing the prepreg, the resin composition according to the present embodiment is often prepared in a varnish state as described above and used as a resin varnish.
[0133] As a method for manufacturing the prepreg 1, specifically, there can be cited a method of impregnating the resin composition 2 (for example, a resin composition 2 modulated into a varnish state) into a fibrous substrate 3 and then drying it. The impregnation of the resin composition 2 into the fibrous substrate 3 is performed by impregnation and coating, etc. The impregnation can also be repeated multiple times as needed. Moreover, at this time, it is also possible to adjust the final desired composition and impregnation amount by repeatedly impregnating with multiple resin compositions with different compositions and concentrations.
[0134] The fibrous substrate 3 impregnated with the resin composition (resin varnish) 2 is heated under the required heating conditions (for example, heating at 40° C. or higher and 180° C. or lower for 1 minute or more and 10 minutes or less). By heating, a prepreg 1 in a pre-cured state (stage A) or a semi-cured state (stage B) can be obtained. It should be noted that by the heating, the organic solvent is volatilized from the resin varnish, and the organic solvent can be reduced or removed.
[0135] The resin composition involved in the present embodiment is a resin composition that can become a relative dielectric constant and a dielectric loss factor that is low, and the relative dielectric constant and the dielectric loss factor caused by water absorption are fully suppressed, and the cured product with a low thermal expansion coefficient. That is, if the resin composition is cured, it becomes a relative dielectric constant and a dielectric loss factor that is low, and the relative dielectric constant and the dielectric loss factor caused by water absorption are fully suppressed, and the cured product with a low thermal expansion coefficient. Therefore, the prepreg of the semi-cured product of the resin composition or the resin composition can obtain a relative dielectric constant and a dielectric loss factor that is low, and the relative dielectric constant and the dielectric loss factor caused by water absorption are fully suppressed, and the cured product with a low thermal expansion coefficient. Specifically, the relative dielectric constant of the cured product of the prepreg at a frequency of 10GHz is preferably less than 3.1, more preferably less than 3. In addition, the dielectric loss factor of the cured product of the prepreg at a frequency of 10 GHz is preferably less than 0.004, and more preferably less than 0.0037. The change in the relative dielectric constant of the cured product after absorbing water (the relative dielectric constant of the cured product after absorbing water - the relative dielectric constant of the cured product before absorbing water) is preferably less than 0.2, and more preferably less than 0.18. The change in the dielectric loss factor of the cured product after absorbing water (the dielectric loss factor of the cured product after absorbing water - the dielectric loss factor of the cured product before absorbing water) is preferably less than 0.013, and more preferably less than 0.011. It should be noted that the relative dielectric constant and dielectric loss factor here are the relative dielectric constant and dielectric loss factor of the cured product of the prepreg at a frequency of 10 GHz, and examples thereof include the relative dielectric constant and dielectric loss factor of the cured product of the prepreg at a frequency of 10 GHz measured by the resonant cavity perturbation method. In addition, the thermal expansion coefficient of the cured product of the prepreg is preferably 150ppm / ℃ or less, more preferably 110ppm / ℃ or less. Therefore, the prepreg having the resin composition or the semi-cured product of the resin composition is a prepreg having a low relative dielectric constant and a low dielectric loss factor, and the increase of the relative dielectric constant and the dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. Therefore, the prepreg can be well manufactured with a wiring board having an insulating layer comprising a cured product having a low relative dielectric constant and a low dielectric loss factor, and the increase of the relative dielectric constant and the dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low.
[0136] [Metal foil laminate]
[0137] Figure 2 It is a schematic cross-sectional view showing an example of the metal foil-clad laminate 11 according to the embodiment of the present invention.
[0138] like Figure 2As shown, the metal-clad laminate 11 according to the present embodiment includes: an insulating layer 12 including a cured product of the resin composition; and a metal foil 13 provided on the insulating layer 12. Examples of the metal-clad laminate 11 include a laminate including Figure 1 An insulating layer 12 of a cured product of the prepreg 1 shown; and a metal foil-clad laminate of a metal foil 13 stacked together with the insulating layer 12. In addition, the insulating layer 12 can be formed by a cured product of the resin composition, or by a cured product of the prepreg. In addition, the thickness of the metal foil 13 varies depending on the performance required of the final wiring board, and is not particularly limited. The thickness of the metal foil 13 can be appropriately set according to the desired purpose, for example, preferably 0.2 to 70 μm. In addition, as the metal foil 13, for example, copper foil and aluminum foil can be listed. When the metal foil is thin, in order to improve the operability, it can be a copper foil with a carrier having a peeling layer and a carrier.
[0139] As a method for manufacturing the metal foil-clad laminate 11, there is no particular limitation as long as the metal foil-clad laminate 11 can be manufactured. Specifically, a method for manufacturing the metal foil-clad laminate 11 using the prepreg 1 can be cited. As this method, a method can be cited as follows: taking a piece of the prepreg 1 or overlapping several pieces of the prepreg 1, and then overlapping a metal foil 13 such as copper foil on the upper and lower surfaces or one side surface thereof, and heating and pressing the metal foil 13 and the prepreg 1 to form a laminate 11 with metal foil on both sides or one side, etc. can be made. That is, the metal foil-clad laminate 11 is obtained by stacking the metal foil 13 on the prepreg 1 and heating and pressing it. In addition, the conditions for heating and pressing can be appropriately set according to the thickness of the metal foil-clad laminate 11 or the type of resin composition contained in the prepreg 1. For example, the temperature can be set to 170 to 230°C, the pressure can be set to 2 to 4MPa, and the time can be set to 60 to 150 minutes. The metal foil-clad laminate may be produced without using a prepreg, for example, by applying a varnish-like resin composition on a metal foil, forming a layer containing the resin composition on the metal foil, and then heating and pressing the layer.
[0140] The resin composition involved in the present embodiment is a resin composition that can become a cured product with low relative dielectric constant and dielectric loss factor, and the rise of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. That is, if the resin composition is cured, relative dielectric constant and dielectric loss factor are low, and the rise of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. Therefore, the metal foil laminated board with the insulating layer of the cured product comprising the resin composition is a metal foil laminated board with the insulating layer of the cured product comprising low relative dielectric constant and dielectric loss factor, and the rise of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. Furthermore, the metal foil-clad laminate can be used to manufacture a wiring board having an insulating layer including a cured product having low relative permittivity and dielectric loss tangent, in which increases in relative permittivity and dielectric loss tangent due to water absorption are sufficiently suppressed, and in which the thermal expansion coefficient is low.
[0141] [Wiring board]
[0142] Figure 3 It is a schematic cross-sectional view showing an example of wiring board 21 according to the embodiment of the present invention.
[0143] like Figure 3 As shown, the wiring board 21 according to the present embodiment includes: an insulating layer 12 including a cured product of the resin composition; and wiring 14 provided on the insulating layer 12. Examples of the wiring board 21 include: Figure 1 The insulating layer 12 used by curing the prepreg 1 shown in the figure; and a wiring board etc. which is laminated together with the insulating layer 12 and forms wiring 14 by removing a part of the metal foil 13. In addition, the insulating layer 12 may be formed of a cured product of the resin composition or a cured product of the prepreg.
[0144] The method for manufacturing the wiring board 21 is not particularly limited as long as the wiring board 21 can be manufactured. Specifically, a method for manufacturing the wiring board 21 using the prepreg 1 can be cited. As this method, for example, a method for manufacturing the wiring board 21 in which wiring is provided as a circuit on the surface of the insulating layer 12 by etching the metal foil 13 on the surface of the metal foil-clad laminate 11 manufactured as described above, and the like can be cited. That is, the wiring board 21 can be obtained by removing a portion of the metal foil 13 on the surface of the metal foil-clad laminate 11, thereby forming a circuit. In addition, as a method for forming a circuit, in addition to the above-mentioned method, a method for forming a circuit by, for example, a semi-additive process (SAP: Semi Additive Process) or a modified semi-additive process (MSAP: Modified Semi Additive Process) can be cited.
[0145] The resin composition involved in the present embodiment is a resin composition that can become a cured product with low relative dielectric constant and dielectric loss factor, and the rise of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. That is, if the resin composition is cured, it becomes a cured product with low relative dielectric constant and dielectric loss factor, and the rise of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. Therefore, the wiring board with an insulating layer of a cured product comprising the resin composition is a wiring board with an insulating layer of a cured product comprising low relative dielectric constant and dielectric loss factor, and the rise of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low.
[0146] The metal foil-clad laminate and the wiring board have the insulating layer as described above. The insulating layer (the insulating layer of the metal foil-clad laminate and the insulating layer of the wiring board) is preferably the following insulating layer. The relative dielectric constant of the insulating layer at a frequency of 10 GHz is preferably 3.1 or less, and more preferably 3 or less. In addition, the dielectric loss factor of the insulating layer at a frequency of 10 GHz is preferably 0.004 or less, and more preferably 0.0037 or less. The change in the relative dielectric constant of the insulating layer after water absorption (the relative dielectric constant of the insulating layer after water absorption - the relative dielectric constant of the insulating layer before water absorption) is preferably 0.2 or less, and more preferably 0.18 or less. The change in the dielectric loss factor of the insulating layer after water absorption (the dielectric loss factor of the insulating layer after water absorption - the dielectric loss factor of the insulating layer before water absorption) is preferably 0.013 or less, and more preferably 0.011 or less. It should be noted that the relative dielectric constant and dielectric loss factor here are the relative dielectric constant and dielectric loss factor of the insulating layer at a frequency of 10 GHz, and examples thereof include the relative dielectric constant and dielectric loss factor of the insulating layer at a frequency of 10 GHz measured by a resonant cavity perturbation method, etc. In addition, the thermal expansion coefficient of the insulating layer is preferably 150 ppm / °C or less, more preferably 110 ppm / °C or less.
[0147] [Metal foil with resin]
[0148] Figure 4 It is a schematic cross-sectional view showing an example of the metal foil with resin 31 according to the present embodiment.
[0149] like Figure 4 As shown in the figure, the metal foil with resin 31 according to the present embodiment comprises: a resin layer 32 containing the resin composition or a semi-cured product of the resin composition; and a metal foil 13. The metal foil with resin 31 has the metal foil 13 on the surface of the resin layer 32. That is, the metal foil with resin 31 comprises: the resin layer 32; and the metal foil 13 laminated together with the resin layer 32. In addition, the metal foil with resin 31 may further comprise another layer between the resin layer 32 and the metal foil 13.
[0150] As the resin layer 32, it may include a semi-cured product of the resin composition as described above, and may also include an uncured resin composition. That is, the metal foil with resin 31 may be a resin layer including a semi-cured product of the resin composition (the resin composition in the B stage); and a metal foil with resin, or may be a resin layer including the resin composition before curing (the resin composition in the A stage); and a metal foil with resin. In addition, as the resin layer, as long as it includes the resin composition or the semi-cured product of the resin composition, it may include or not include a fibrous substrate. In addition, as the resin composition or the semi-cured product of the resin composition, it may be a substance obtained by drying or heat-drying the resin composition. In addition, as the fibrous substrate, the same material as the fibrous substrate of the prepreg can be used.
[0151] As the metal foil, metal foils used in metal foil-clad laminates and metal foils with resins can be used without limitation. Examples of the metal foil include copper foil and aluminum foil.
[0152] The metal foil with resin 31 may be provided with a covering film etc. as required. By providing the covering film, it is possible to prevent the mixing of foreign matter etc. The covering film is not particularly limited, and examples thereof include polyolefin films, polyester films, polymethylpentene films, and films formed by providing a release agent layer on these films.
[0153] The method for manufacturing the metal foil 31 with resin is not particularly limited as long as the metal foil 31 with resin can be manufactured. As the method for manufacturing the metal foil 31 with resin, there can be cited a method of applying the above-mentioned varnish-like resin composition (resin varnish) on the metal foil 13 and heating it. For example, the varnish-like resin composition is applied to the metal foil 13 using a scraper coater. The applied resin composition is heated under conditions of, for example, 40°C to 180°C and 0.1 minutes to 10 minutes. The heated resin composition is formed on the metal foil 13 as an uncured resin layer 32. It should be noted that by the heating, the organic solvent is volatilized from the resin varnish, and the organic solvent can be reduced or removed.
[0154] The resin composition involved in the present embodiment is a resin composition that can become a cured product with low relative dielectric constant and dielectric loss factor, and the rise of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. That is, if the resin composition is cured, it becomes a cured product with low relative dielectric constant and dielectric loss factor, and the rise of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. Therefore, the metal foil with resin having a resin layer containing the resin composition or the semi-cured product of the resin composition is a metal foil with resin having an insulating layer containing a resin layer that can obtain a cured product with low relative dielectric constant and dielectric loss factor, and the rise of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. Furthermore, the metal foil with resin can be used in manufacturing a wiring board having a cured product with low relative dielectric constant and dielectric loss factor, and the increase of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. For example, a multilayer wiring board can be manufactured by stacking on a wiring board. As a wiring board obtained by using the metal foil with resin, a wiring board having an insulating layer including a cured product with low relative dielectric constant and dielectric loss factor, and the increase of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low can be obtained.
[0155] [Film with resin]
[0156] Figure 5 It is a schematic cross-sectional view showing an example of the film 41 with resin according to the present embodiment.
[0157] like Figure 5 As shown in FIG. 1 , the film 41 with resin according to the present embodiment includes: a resin layer 42 including the resin composition or a semi-cured product of the resin composition; and a support film 43. The film 41 with resin includes: the resin layer 42; and the support film 43 laminated together with the resin layer 42. In addition, the film 41 with resin may further include another layer between the resin layer 42 and the support film 43.
[0158] As the resin layer 42, it may include a semi-cured product of the resin composition as described above, and may also include an uncured resin composition. That is, the film 41 with resin may be a film with resin including: a resin layer including a semi-cured product of the resin composition (the resin composition in the B stage); and a supporting film, or may be a film with resin including: a resin layer including the resin composition before curing (the resin composition in the A stage); and a supporting film. In addition, as the resin layer, as long as it includes the resin composition or the semi-cured product of the resin composition, it may include or not include a fibrous substrate. In addition, as the resin composition or the semi-cured product of the resin composition, it may be a substance obtained by drying or heat-drying the resin composition. In addition, as the fibrous substrate, the same material as the fibrous substrate of the prepreg can be used.
[0159] As the supporting film 43, any supporting film used in a film with a resin can be used without limitation. Examples of the supporting film include electrically insulating films such as polyester films, polyethylene terephthalate (PET) films, polyimide films, polyoxalyl urea films, polyetheretherketone films, polyphenylene sulfide films, polyamide films, polycarbonate films, and polyarylate films.
[0160] The film 41 with resin may include a cover film etc. as needed. By including the cover film, it is possible to prevent foreign matter from being mixed in. The cover film is not particularly limited, and examples thereof include polyolefin films, polyester films, and polymethylpentene films.
[0161] The supporting film and the cover film may be films subjected to surface treatment such as matte treatment, corona treatment, mold release treatment, and roughening treatment as required.
[0162] The method for manufacturing the resin-bearing film 41 is not particularly limited as long as the resin-bearing film 41 can be manufactured. The method for manufacturing the resin-bearing film 41 may include, for example, a method of applying the above-mentioned varnish-like resin composition (resin varnish) on the supporting film 43 and heating it. For example, the varnish-like resin composition is applied to the supporting film 43 using a scraper coater. The applied resin composition is heated under conditions of, for example, 40°C to 180°C and 0.1 minutes to 10 minutes. The heated resin composition is formed on the supporting film 43 as an uncured resin layer 42. It should be noted that by volatilizing the organic solvent from the resin varnish through the heating, the organic solvent can be reduced or removed.
[0163] The resin composition involved in the present embodiment is a resin composition that can obtain a low relative dielectric constant and dielectric loss factor, and the rise of the relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the cured product with a low thermal expansion coefficient. That is, if the resin composition is cured, it becomes a low relative dielectric constant and dielectric loss factor, and the rise of the relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the cured product with a low thermal expansion coefficient. Therefore, the film with a resin layer of a semi-cured product including the resin composition or the resin composition is a film with a resin layer of an insulating layer that can obtain a low relative dielectric constant and dielectric loss factor, and the rise of the relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the cured product with a low thermal expansion coefficient. Furthermore, the film with resin can be used to manufacture a wiring board having an insulating layer with a low relative dielectric constant and dielectric loss factor, and the increase of the relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. For example, a multilayer wiring board can be manufactured by peeling off the supporting film after being stacked on the wiring board, or by peeling off the supporting film and stacking on the wiring board. As a wiring board obtained by using the film with resin, a wiring board having an insulating layer with a low relative dielectric constant and dielectric loss factor, and the increase of the relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low.
[0164] As described above, this specification discloses the techniques of various embodiments, and the main techniques are summarized as follows.
[0165] The first technical solution relates to a resin composition, which contains: a maleimide compound (A) having a benzene ring in the molecule and a maleimide equivalent of less than 500 g / mol; an imide compound (B) having at least one of a hydrocarbon group and a maleimide group at the end of the molecule; and a free radical polymerizable compound (C) having a benzene ring bonded to an alkenyl group in the molecule and a weight average molecular weight of less than 1000.
[0166] The resin composition according to the second invention is the resin composition according to the first invention, wherein the imide compound (B) has a structure represented by the following formula (1) in the molecule.
[0167]
[0168] In formula (1), X1 represents a tetravalent tetracarboxylic acid residue, X2 represents a divalent aliphatic diamine residue, X3 represents a divalent aromatic diamine residue, X4 and X5 each independently represent a hydrocarbon group having 1 to 20 carbon atoms, a maleimide group or an acid anhydride group, at least one of X4 and X5 represents a hydrocarbon group having 1 to 20 carbon atoms or a maleimide group, m represents 1 to 50, n represents 0 to 49, and the total of m and n represents 1 to 50.
[0169] The resin composition according to the third invention is the resin composition according to the first or second invention, wherein the weight average molecular weight of the imide compound (B) is 10,000 to 30,000.
[0170] The resin composition according to a fourth aspect is the resin composition according to any one of the first to third aspects, wherein the maleimide compound (A) contains a maleimide compound having an arylene structure bonded in an aligned manner at a meta position in the molecule.
[0171] A resin composition according to a fifth aspect is the resin composition according to any one of the first to fourth aspects, wherein the alkenyl group in the radical polymerizable compound (C) includes at least one selected from the group consisting of an allyl group, a vinyl group, and a propenyl group.
[0172] The resin composition involved in the sixth technical solution is the resin composition involved in any one of the first to fifth technical solutions, wherein the content of the maleimide compound (A) is 30 to 70 parts by mass relative to 100 parts by mass of the total of the maleimide compound (A), the imide compound (B) and the free radical polymerizable compound (C).
[0173] The resin composition involved in the seventh technical solution is the resin composition involved in any one of the first to sixth technical solutions, wherein the content of the imide compound (B) is 10 to 40 parts by mass relative to 100 parts by mass of the total of the maleimide compound (A), the imide compound (B) and the free radical polymerizable compound (C).
[0174] The resin composition according to the eighth invention is the resin composition according to any one of the first to seventh inventions, further comprising an inorganic filler.
[0175] A ninth technical solution is directed to a prepreg comprising: the resin composition according to any one of the first to eighth technical solutions or a semi-cured product of the resin composition; and a fibrous base material.
[0176] A tenth invention relates to a film with a resin, comprising: a resin layer comprising the resin composition according to any one of the first to eighth inventions or a semi-cured product of the resin composition; and a support film.
[0177] The eleventh invention relates to a metal foil with resin, comprising: a resin layer containing the resin composition according to any one of the first to eighth inventions or a semi-cured product of the resin composition; and a metal foil.
[0178] A twelfth invention relates to a metal-clad laminate comprising: an insulating layer comprising a cured product of the resin composition according to any one of the first to eighth inventions; and a metal foil.
[0179] A thirteenth invention relates to a metal foil-clad laminate comprising: an insulating layer formed from a cured product of the prepreg according to the ninth invention; and a metal foil.
[0180] A fourteenth invention relates to a wiring board comprising: an insulating layer formed of a cured product of the resin composition according to any one of the first to eighth inventions; and wiring.
[0181] A fifteenth technical solution is directed to a wiring board comprising: an insulating layer formed of a cured product of the prepreg according to the ninth technical solution; and wiring.
[0182] According to the present invention, a resin composition can be provided that can obtain a cured product having low relative dielectric constant and dielectric loss factor, in which the increase of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. In addition, according to the present invention, a prepreg, a film with resin, a metal foil with resin, a metal foil-clad laminate, and a wiring board obtained by using the resin composition can be provided.
[0183] Hereinafter, the present invention will be further specifically described by way of examples; however, the scope of the present invention is not limited to these examples.
[0184] Example
[0185] [Examples 1 to 12, Comparative Examples 1 and 2]
[0186] Each component used to prepare the resin composition in this example is described.
[0187] (Maleimide compound)
[0188] Maleimide compound: a maleimide compound having an arylene structure bonded in a directional manner at the meta position in the molecule (the maleimide compound represented by the above formula (4), the solid content in MIR-5000-60T (a toluene-soluble composition of a maleimide compound) manufactured by Nippon Kayaku Co., Ltd.)
[0189] (Imide compound)
[0190] Imido compound-1: an imide compound represented by the above formula (1) having a structure in which X4 and X5 are hydrocarbon groups in the molecule (VA-9601 manufactured by Toyochem Co., Ltd., acid value: 1.0 mgKOH / g, weight average molecular weight: 24000)
[0191] Imidide compound-2: an imide compound represented by the above formula (1) having a structure in which X4 and X5 are hydrocarbon groups in the molecule (VA-9603 manufactured by Toyochem Co., Ltd., acid value: 3.4 mgKOH / g, weight average molecular weight: 12000)
[0192] Imido compound-3: an imide compound represented by the above formula (1) having a structure in which X4 and X5 are hydrocarbon groups in the molecule (VA-9604 manufactured by Toyochem Co., Ltd., acid value: 0.6 mgKOH / g, weight average molecular weight: 11000)
[0193] Imidide compound-4: an imide compound having a maleimide group at a molecular terminal (a maleimide compound represented by the following formula (10), BMI-3000J manufactured by Desingner Molecules Inc.)
[0194]
[0195] In the formula (10), x as a repeating unit represents 1 to 10.
[0196] Imidide compound-5: an imide compound having a maleimide group at a molecular terminal (a maleimide compound represented by the following formula (11), BMI-1500 manufactured by Designer Molecular Co., Ltd.).
[0197]
[0198] In the formula (11), y as a repeating unit represents 1 to 10.
[0199] (Radical polymerizable compound)
[0200] Benzoxazine compound: a benzoxazine compound having an allyl group in the molecule (a benzoxazine compound represented by the above formula (6) in which X6 is a methylene group, q and r are 1, ALPd manufactured by Shikoku Chemicals Co., Ltd.)
[0201] Hydrocarbon compound-1: a hydrocarbon compound represented by the above formula (8).
[0202] Specifically, it is a hydrocarbon compound synthesized as follows.
[0203] (Synthesis example 1)
[0204] In a flask equipped with a thermometer, a cooling tube and a stirrer, 296 parts by mass of 2-bromoethylbenzene (manufactured by Tokyo Chemical Industry Co., Ltd.), 70 parts by mass of α,α'-dichloroparaxylene (manufactured by Tokyo Chemical Industry Co., Ltd.), and 18.4 parts by mass of methanesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added, and the mixture was reacted at 130°C for 8 hours. After the reaction was completed, the mixture was cooled, and then the reaction solution obtained by the reaction was neutralized with an aqueous sodium hydroxide solution, extracted with 1200 parts by mass of toluene, and the organic layer was washed 5 times with 100 parts by mass of water. The solvent and excess 2-bromoethylbenzene were distilled off under reduced pressure with heating, thereby obtaining 160 parts by mass of an olefin compound precursor (BEB-1) having a 2-bromoethylbenzene structure as a liquid resin (Mn: 538, Mw: 649). The GPC spectrum of the obtained compound was obtained, and the repeating unit n calculated based on the area % of the obtained GPC spectrum was 1.7. In addition, the 1 H-NMR spectrum (DMSO-d6), and in the obtained 1 In the H-NMR spectrum, signals derived from the bromoethyl group were observed at 2.95-3.15 ppm and 3.60-3.75 ppm.
[0205] (Synthesis example 2)
[0206] Next, 22 parts by mass of BEB-1 obtained in the above-mentioned Synthesis Example 1, 50 parts by mass of toluene, 150 parts by mass of dimethyl sulfoxide, 15 parts by mass of water, and 5.4 parts by mass of sodium hydroxide were added to a flask equipped with a thermometer, a cooling tube, and a stirrer, and the mixture was reacted at 40°C for 5 hours. After the reaction was completed, the mixture was allowed to cool, and then 100 parts by mass of toluene were added, and the organic layer was washed 5 times with 100 parts by mass of water. The solvent was removed by distillation under reduced pressure while heating, thereby obtaining 13 parts by mass of a liquid olefin compound having a styrene structure as a functional group (Mn: 432, Mw: 575). The GPC spectrum of the obtained compound was obtained, and the repeating unit n calculated based on the area % of the obtained GPC spectrum was 1.7. In addition, the 1 H-NMR spectrum (DMSO-d6), and in the obtained 1 In the H-NMR spectrum, signals derived from the vinyl group were observed at 5.10-5.30 ppm, 5.50-5.85 ppm, and 6.60-6.80 ppm.
[0207] The obtained compound (liquid olefin compound) is a hydrocarbon compound represented by the above formula (8).
[0208] It should be noted that the weight average molecular weight (Mw) and number average molecular weight (Mn) used in Synthesis Example 1 and Synthesis Example 2 are values obtained by the following analysis method.
[0209] (Analytical method)
[0210] The amount was calculated by polystyrene conversion using a polystyrene standard solution.
[0211] GPC: DGU-20A3R, LC-20AD, SIL-20AHT, RID-20A, SPD-20A, CTO-2, CBM-20A (all manufactured by Shimadzu Corporation)
[0212] Chromatographic columns: Shodex KF-603, KF-602x2, KF-601x2
[0213] Coupled eluent: tetrahydrofuran
[0214] Flow rate: 0.5ml / min
[0215] Column temperature: 40°C
[0216] Detection: RI (Refractive Index Detector)
[0217] Hydrocarbon compound-2: 1,2-bis(vinylphenyl)ethane (BVPE) (a compound represented by the above formula (9) where b is 2). Specifically, BVPE is produced by subjecting chloromethylvinylbenzene (vinylbenzylchloride) such as 1-(chloromethyl)-4-vinylbenzene to a Grignard reaction.
[0218] Specifically, hydrocarbon compound-2 was produced as follows.
[0219] First, 5.36 g (220 mmol) of granular magnesium for Grignard reaction (manufactured by Kanto Chemical Co., Ltd.) was placed in a 500 ml three-necked flask, and a dropping funnel, a nitrogen introduction tube, and a septum cap were installed.
[0220] In the three-necked flask, the granular magnesium was stirred with a stirrer under a nitrogen flow and the whole system was heated with a dryer to dehydrate. Then, 300 ml of dry tetrahydrofuran was taken with a syringe and injected into the three-necked flask through the septum cap.
[0221] After the solution in the three-necked flask was cooled to -5°C, 30.5 g (200 mmol) of chloromethylvinylbenzene (manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise to the solution using a dropping funnel over a period of about 4 hours. After the addition was completed, stirring was continued at 0°C for 20 hours to allow the chloromethylvinylbenzene to react. After the reaction was completed, the solution obtained by the reaction was filtered to remove the residual magnesium and concentrated using an evaporator. The concentrated solution was diluted with hexane, washed once with a 3.6% hydrochloric acid aqueous solution, washed three times with pure water, and then dehydrated with magnesium sulfate. The dehydrated solution was purified by passing through a short column of silica gel (Wakogel C300 manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) / hexane and vacuum dried to obtain BVPE.
[0222] Modified PPE: a polyphenylene ether compound having a vinylbenzyl group (vinylbenzyl group) at a molecular terminal (styrene-modified polyphenylene ether) (OPE-2st 1200 manufactured by Mitsubishi Gas Chemical Co., Ltd.)
[0223] (Reaction initiator)
[0224] PBP: α,α'-di(tert-butylperoxy)diisopropylbenzene (PERBUTYL P(PBP) manufactured by NOF Corporation)
[0225] (Curing accelerator)
[0226] 2E4MZ: 2-ethyl-4-methylimidazole (2E4MZ manufactured by Shikoku Chemical Industry Co., Ltd.)
[0227] (Inorganic filler)
[0228] Silica: K180SV-C2 manufactured by Admatechs Company Limited
[0229] [Preparation method]
[0230] First, each component except the inorganic filler was added to toluene, methyl ethyl ketone, or a mixed solvent of toluene and methyl ethyl ketone in the composition (parts by mass) described in Table 1 and Table 2 and mixed so that the solid content concentration was 40 to 60% by mass. The mixture was stirred for 60 minutes. Then, in the case of containing an inorganic filler, the inorganic filler was added to the resulting liquid, and the inorganic filler was dispersed with a bead mill. By doing so, a varnish-like resin composition (varnish) was obtained.
[0231] Next, the obtained varnish was impregnated into glass cloth (#1067 type, NE glass manufactured by Nitto Bo Co., Ltd.), and then heated and dried at 100 to 160°C for about 2 to 8 minutes to obtain a prepreg. At this time, the thickness of the prepreg after curing was adjusted to be about 76 μm (the content of the organic component in the resin composition was about 71 to 74% by mass).
[0232] (Evaluation substrate 1)
[0233] Then, four sheets of each of the obtained prepregs were stacked, and metal foils (MT18FL 1.5 manufactured by Mitsui Mining & Smelting Co., Ltd., 1.5 μm thick copper foil with a carrier foil of 18 μm thickness) were arranged on both sides as a pressurized body, and heated and pressed for 2 hours at a temperature of 220° C. and a pressure of 2 MPa to produce a copper-clad laminate (metal-clad laminate) with a thickness of about 0.3 mm and copper foil bonded to both surfaces. The obtained copper-clad laminate was used as an evaluation substrate 1.
[0234] (Evaluation substrate 2)
[0235] A copper-clad laminate (metal-clad laminate) having a thickness of about 1 mm was obtained by the same method as the method for producing the evaluation substrate 1 except that the number of stacked prepreg sheets was changed from 4 to 14. The obtained copper-clad laminate was used as the evaluation substrate 2.
[0236] The evaluation substrate (metal foil-clad laminate) prepared as described above was evaluated by the method shown below.
[0237] [Dielectric properties (relative dielectric constant and dielectric loss factor)]
[0238] Copper foil was removed from the evaluation substrate 1 (metal foil laminate) by etching. The substrate thus obtained was used as a test piece, and the relative dielectric constant and dielectric loss factor at 10 GHz were determined by the resonant cavity perturbation method. Specifically, a network analyzer (N5230A manufactured by Keysight Technologies Co., Ltd.) was used to determine the relative dielectric constant (Dk) and dielectric loss factor (Df) of the test piece at 10 GHz. The relative dielectric constant and dielectric loss factor were measured before and after water absorption.
[0239] Furthermore, the difference between the relative dielectric constant of the test piece after water absorption and the relative dielectric constant of the test piece before water absorption was calculated. Furthermore, the difference between the dielectric loss tangent of the test piece after water absorption and the dielectric loss tangent of the test piece before water absorption was calculated.
[0240] If the relative dielectric constant obtained by measurement (the relative dielectric constant of the test piece before water absorption) is 3.1 or less, it is judged as "qualified". In addition, if the dielectric loss factor obtained by measurement (the dielectric loss factor of the test piece before water absorption) is 0.004 or less, it is judged as "qualified". In addition, if the change in the relative dielectric constant after the test piece absorbs water (the relative dielectric constant of the test piece after water absorption - the relative dielectric constant of the test piece before water absorption) is 0.2 or less, it is judged as "qualified". If the change in the dielectric loss factor after the test piece absorbs water (the dielectric loss factor of the test piece after water absorption - the dielectric loss factor of the test piece before water absorption) is 0.013 or less, it is judged as "qualified".
[0241] [Coefficient of thermal expansion]
[0242] The bare board from which the copper foil was removed from the evaluation substrate 2 (metal foil-clad laminate) by etching was used as a test piece, and the thermal expansion coefficient (CTE: ppm / °C) in the Z-axis direction was measured by TMA method (Thermo-mechanical analysis). During the measurement, a TMA device (TMA7100 manufactured by Seiko Nanotech Corporation) was used, and the temperature was heated from room temperature to 265°C at a heating rate of 20°C / min, cooled to room temperature, and then increased at a heating rate of 10°C / min, and the measurement was performed in the range of 50 to 260°C.
[0243] [Dispersion state]
[0244] The entire surface of the evaluation substrate 1 (metal foil-clad laminate) was covered with an embedding resin. The evaluation substrate covered with the embedding resin was polished to expose the cross section of the evaluation substrate. The cross section of the evaluation substrate exposed on the polished surface was observed using a desktop microscope (TM4000plus manufactured by Hitachi High-Technologies Corporation) at an accelerating voltage of 5 to 15 kV and a magnification of 1000 times.
[0245] When an inorganic filler is contained, the maximum area in the region where the inorganic filler is not confirmed is 10 μm. 2 If the area is larger than 10 μm, the evaluation is “uneven”. In addition, the largest area in the area where the inorganic filler is not confirmed is less than 10 μm. 2 When the area was uniform and the area could not be distinguished (such as an area where the inorganic filler was not confirmed and an area where the inorganic filler was confirmed), it was evaluated as "uniform".
[0246] In the case where no inorganic filler is included, the maximum area in the region where unevenness of the resin density is observed is 10 μm. 2If the area is larger than 10 μm, the evaluation is “uneven”. In addition, the largest area in the area where the presence of unevenness of the resin density is confirmed is less than 10 μm. 2 When the area was uniform and when no areas (areas where the presence of unevenness in resin density was confirmed and areas where the presence of unevenness in resin density was not confirmed, etc.) could be distinguished (that is, when unevenness in resin density was not confirmed), it was evaluated as “uniform”.
[0247] Tables 1 and 2 show the results of the above evaluations.
[0248]
[0249]
[0250] As can be seen from Tables 1 and 2, the case containing the maleimide compound (A), the imide compound (B) and the radically polymerizable compound (C) (Examples 1 to 12) compared with the case not containing them (the case containing a radically polymerizable compound different from the radically polymerizable compound (C): Comparative Example 1, and the case not containing the imide compound (B): Comparative Example 2) provides a resin composition that has a low relative dielectric constant and a low dielectric loss tangent, and in which the increase in the relative dielectric constant and the dielectric loss tangent due to water absorption is fully suppressed, and a cured product with a low thermal expansion coefficient is obtained.
[0251] This application is based on Japanese invention patent application No. 2022-107976 filed on July 4, 2022, and the contents are included in this application.
[0252] In order to describe the present invention, the present invention has been appropriately and fully described above through the embodiments, but it should be recognized that those skilled in the art can easily change and / or improve the above embodiments. Therefore, the changed embodiments or improved embodiments implemented by those skilled in the art, as long as they do not deviate from the protection scope of the claims recorded in the claims, the changed embodiments or the improved embodiments can be interpreted as being included in the protection scope of the claims.
[0253] Industrial Applicability
[0254] According to the present invention, a resin composition can be provided that can obtain a cured product having low relative dielectric constant and dielectric loss factor, in which the increase of relative dielectric constant and dielectric loss factor due to water absorption is fully suppressed, and the thermal expansion coefficient is low. In addition, according to the present invention, a prepreg, a film with resin, a metal foil with resin, a metal foil-clad laminate, and a wiring board obtained using the resin composition can be provided.
Claims
1. A resin composition, characterized in that contain: The maleimide compound (A) has a benzene ring in the molecule and a maleimide equivalent of 500 g / mol or less; An imide compound (B) having at least one of a hydrocarbon group and a maleimide group at a molecular terminal; as well as The radical polymerizable compound (C) has a benzene ring bonded to an alkenyl group in the molecule, and has a weight average molecular weight of 1,000 or less.
2. The resin composition according to claim 1, characterized in that The imide compound (B) has a structure represented by the following formula (1) in the molecule: In formula (1), X1 represents a tetravalent tetracarboxylic acid residue, X2 represents a divalent aliphatic diamine residue, X3 represents a divalent aromatic diamine residue, X4 and X5 each independently represent a hydrocarbon group having 1 to 20 carbon atoms, a maleimide group or an acid anhydride group, at least one of X4 and X5 represents a hydrocarbon group having 1 to 20 carbon atoms or a maleimide group, m represents 1 to 50, n represents 0 to 49, and the total of m and n represents 1 to 50.
3. The resin composition according to claim 1, characterized in that The weight average molecular weight of the imide compound (B) is 10,000 to 30,000.
4. The resin composition according to claim 1, characterized in that The maleimide compound (A) includes a maleimide compound having an arylene structure bonded in a directional manner at a meta position in the molecule.
5. The resin composition according to claim 1, characterized in that The alkenyl group in the radical polymerizable compound (C) includes at least one selected from the group consisting of an allyl group, a vinyl group, and a propenyl group.
6. The resin composition according to claim 1, characterized in that The content of the maleimide compound (A) is 30 to 70 parts by mass based on 100 parts by mass of the total of the maleimide compound (A), the imide compound (B), and the radical polymerizable compound (C).
7. The resin composition according to claim 1, characterized in that The content of the imide compound (B) is 10 to 40 parts by mass based on 100 parts by mass of the total of the maleimide compound (A), the imide compound (B), and the radical polymerizable compound (C).
8. The resin composition according to claim 1, characterized in that Also contains: Inorganic filler materials.
9. A prepreg, characterized in that include: The resin composition according to any one of claims 1 to 8 or a semi-cured product of the resin composition; as well as Cellulosic substrate.
10. A film with resin, characterized in that include: A resin layer comprising the resin composition according to any one of claims 1 to 8 or a semi-cured product of the resin composition; and Support membrane.
11. A metal foil with resin, characterized in that include: A resin layer comprising the resin composition according to any one of claims 1 to 8 or a semi-cured product of the resin composition; as well as Metal foil.
12. A metal foil-clad laminate, characterized in that include: An insulating layer comprising a cured product of the resin composition according to any one of claims 1 to 8; and metal foil.
13. A metal foil-clad laminate, characterized in that include: An insulating layer comprising a cured product of the prepreg according to claim 9; as well as Metal foil.
14. A wiring board, characterized in that include: An insulating layer comprising a cured product of the resin composition according to any one of claims 1 to 8; as well as wiring.
15. A wiring board, characterized in that include: An insulating layer comprising a cured product of the prepreg according to claim 9; as well as wiring.
Citation Information
Patent Citations
Situation detection method at passenger conveyor exit
JP2022107976A
Resin composition, support with resin layer, prepreg, laminate, multilayered printed wiring board, and printed wiring board for millimeter-wave radar
WO2016114286A1
Resin composition, and prepreg, resin-coated film, resin-coated metal foil, metal-clad laminate, and wiring board each obtained using said resin composition
WO2019188189A1